1991
DOI: 10.1115/1.2906241
|View full text |Cite
|
Sign up to set email alerts
|

Exhaust Gas Emissions of Butanol, Ethanol, and Methanol-Gasoline Blends

Abstract: Emissions levels for CO, NOx, and unburned fuel (UBF) from a stationary four-cylinder Chrysler engine were measured under a variety of operating conditions for gasoline and three different 20 vol percent alcohol-gasoline blends. In tests of separate isobutanol, ethanol, and methanol blends, lower CO and NOx emissions were observed for the alcohol blends relative to gasoline, particularly for fuel-rich operation. Generally, on a volume (mole) basis unburned fuel emissions were highest for methanol blends and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(59 citation statements)
references
References 0 publications
3
47
0
Order By: Relevance
“…Cases 5 and 6 (which have water injection) indicate relative reductions of 10.4% and 25.3% in NOx emissions, respectively. The ethanol content itself demonstrated a decrease in NOx emission; this observation is consistent with some of the previous studies [10][11][12][13][14] and is primarily due to high heat of vaporization of ethanol compared to gasoline, which decreases the charge temperature [15].…”
Section: Combustion E Ciencysupporting
confidence: 80%
See 1 more Smart Citation
“…Cases 5 and 6 (which have water injection) indicate relative reductions of 10.4% and 25.3% in NOx emissions, respectively. The ethanol content itself demonstrated a decrease in NOx emission; this observation is consistent with some of the previous studies [10][11][12][13][14] and is primarily due to high heat of vaporization of ethanol compared to gasoline, which decreases the charge temperature [15].…”
Section: Combustion E Ciencysupporting
confidence: 80%
“…This was attributed to a faster ame speed, which produced a higher peak pressure and, therefore, a higher peak temperature in the combustion process. However, there are some discrepancies in the literature on the e ect of ethanol on NOx emissions of SI engines [10], and there are a number of other studies that have demonstrated a reduction in NOx emissions using ethanol gasoline blends [11][12][13][14]. This has been attributed to high heat of vaporization of ethanol compared to gasoline, which decreases the charge temperature and reduces thermal NOx formation [15].…”
Section: Introductionmentioning
confidence: 87%
“…Specifically, many of the theoretical and experimental studies evaluating the potential of alcohols are based on ethanol [8][9][10][11][12][13][14][15][16], while other studies have been performed on butanol-fueled engines [17][18][19][20][21], or on assessing n-butanol as a blending agent with gasoline [22][23][24][25][26]. Ethanol can be used as a neat fuel in spark-ignited engines or blended up to 40% with diesel fuel for use in compression-ignition (CI) engines [8][9][10][11][12][13][14][15][16]. Ethanol is biodegradable, it is less detrimental to ground water, and it has an octane number higher than gasoline with positive effect on vehicle emissions [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already been performed in order to investigate the use of both types of alcohols in spark-ignited engines, either blended with gasoline [8][9][10][11][12][13][14][15][16][17][18][19][20][21] or as a neat fuel [22][23][24][25][26]. A review of ethanol/gasoline blends impact on performance and emissions of a spark-ignited engine is given in [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been exploited to investigate the influence of methanol and ethanol on the performance of gasoline fueled spark ignition engines [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Ashraf [9] investigated the performance and exhaust emissions from spark-ignition engine fueled with ethanol-methanol-gasoline blends.…”
mentioning
confidence: 99%